Extração de matéria orgânica aquática por abaixamento de temperatura: Uma metodologia alternativa para manter a identidade da amostra - De Almeida, Rosana N. H. Martins; Mozeto, Antonio Aparecido; Zara, Luiz Fabrício; Rosa, André Henrique [UNESP]; Rocha, Julio Cesar [UNESP]; Cruz Romão, Luciane Pimenta; Sargentini Jr., Ézio (FapUNIFESP (SciELO), 2003)
In this work was developed an alternative methodology to separation of aquatic organic matter (AOM) present in natural river waters. The process is based in temperature decreasing of the aqueous sample under controlled conditions that provoke the freezing of the sample and separation of the dark extract, not frozen and rich in organic matter. The results showed that speed of temperature decreasing exerts strongly influence in relative recovery of organic carbon, enrichment and time separation of the organic matter present in water samples. Elemental composition, infrared spectra and thermal analysis results showed that the alternative methodology is less aggressive possible in the attempt of maintaining the integrity of the sample.
Extraction of aquatic organic matter by temperature decreasing: An alternative methodology to keep the original sample characteristics
Keywords: Aquatic organic matter; Extraction; Humic substances; organic carbon; organic matter; river water; aqueous solution; chemical composition; extraction; freezing; infrared spectroscopy; methodology; separation technique; temperature dependence; thermal analysis; water analysis; water sampling